Long-Term Anabolic Androgenic Steroid Use Is Associated with Increased Atrial Electromechanical Delay in Male Bodybuilders. (4th May 2014) - Akçakoyun, Mustafa; Alizade, Elnur; Gündoğdu, Recep; Bulut, Mustafa; Tabakcı, Mehmet Mustafa; Açar, Göksel; Avcı, Anıl; Şimşek, Zeki; Fidan, Serdar; Demir, Serdar; Kargın, Ramazan; Emiroğlu, Mehmet Yunus
Abstract : We investigated the effect of long-term supraphysiologic doses of anabolic androgenic steroids (AAS) on atrial electromechanical delay (AEMD) in male bodybuilders. We clearly demonstrated that long-term consumption of supraphysiologic doses of AAS is associated with higher values of inter- and intra-AEMD in healthy young bodybuilders.